Fluoroquinolone resistance detection in Mycobacterium tuberculosis with locked nucleic acid probe real-time PCR. - Van Doorn, H; An, D; Jong, d; Lan, N; Hoa, D; Quy, H; Chau, N; Duy, P; Tho, D; Chinh, N; Farrar, J; Caws, M (2008)
SETTING: Pham Ngoc Thach Hospital for Tuberculosis and Lung Diseases, Ho Chi Minh City, Vietnam. OBJECTIVE: Fluoroquinolones (FQs) are increasingly used in the treatment of tuberculosis (TB) and are the second-line drugs of choice for treatment of multidrug-resistant TB. We aimed to set up a polymerase chain reaction (PCR) based assay to detect the most common FQ-resistance-associated mutations in gyrase A (gyrA) of Mycobacterium tuberculosis. DESIGN: A total of 42 FQ-resistant and 40 FQ-susceptible isolates were collected in 2005-2006 and sequenced in gyrA. Using sequencing results as gold standard, a real-time PCR using three locked nucleic acid probes (LNA-PCR) was designed to detect mutations at positions 90, 91 and 94 (97% of gyrA FQ-resistance-associated mutations) and evaluated. RESULTS: Sequencing of 42 FQ-resistant isolates revealed no gyrA mutations in 10 isolates, 20 isolates had a single mutation and 12 isolates showed double peaks at resistance-associated alleles, suggesting a heterogeneous population. With LNA-PCR, all wild-type and 19/20 mutant isolates were correctly identified. Eleven of 12 heterogeneous isolates were correctly identified as resistant mutants. Overall, 71% ([19 + 11]/42) of phenotypically FQ-resistant isolates were detected. Specificity was 100% on 40 FQ-susceptible isolates. CONCLUSION: This assay provides a simple and rapid means to reliably detect FQ-resistance-associated gyrA mutations in M. tuberculosis.